Pengaruh Gerakan Buruh Filipina dan Indonesia Terhadap Kebijakan Negara dalam Penempatan dan Perlindungan Buruh Migran - , AZHAR IRFANSYAH; , Dr. Eric Hiariej, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Philippines and Indonesia are part of the Southeast Asia region with similarities in economic condition. Both countries also known as sending countries of migrant workers and intervene the process of workersâ migration since 1970s. Philippines tends to more focus on protection while Indonesia tends to more focus on placement business. As the result, overseas Filipino workers are more protected while Indonesian migrant workers are prone to be exploited. One of the determined factor which allow this differrence is the militancy and scope of the workers movement in each country as they struggling as a social class.